Core data set on safety, efficacy, and durability of hemophilia gene therapy for a global registry: Communication from the SSC of the ISTH. (29th October 2020) - Konkle, Barbara; Pierce, Glen; Coffin, Donna; Naccache, Mayss; Clark, R. Cary; George, Lindsey; Iorio, Alfonso; O'Mahony, Brian; Pipe, Steven; Skinner, Mark; Watson, Crystal; Peyvandi, Flora; et al.
Abstract: Background: Gene therapy for people with hemophilia (PWH) will soon become available outside current clinical trials. The World Federation of Hemophilia (WFH), in collaboration with International Society of Thrombosis and Hemostasis Scientific and Standardization Committee (ISTH SSC), the European Haemophilia Consortium (EHC), the US National Hemophilia Foundation (NHF), the American Thrombosis and Hemostasis Network (ATHN), industry gene therapy development partners and Regulatory liaisons have developed the Gene Therapy Registry (GTR), designed to collect long‐term data on all PWH who receive hemophilia gene therapy. Objective: The objectives of the GTR are to record the long‐term safety and efficacy data post gene therapy infusion and to assess the changes in quality of life and burden of disease post‐gene‐therapy infusion. Methods: The GTR is a prospective, observational, and longitudinal registry developed under the guidance of a multi‐stakeholder GTR Steering Committee (GTR SC), composed of health care professionals, patient advocates, industry representatives, and regulatory agency liaisons. All PWH who receive gene therapy by clinical trial or commercial product will be invited to enrol in the registry through their hemophilia treatment centers (HTCs). The registry aims to recruit 100% of eligible post gene therapy PWH globally. Through an iterative process, and following the guidance of the European Medicines Agency (EMA) and the US Food and Drug Administration (FDA), the GTR SC has developed a core set of data to be collected on all patients post gene therapy. Results: The core data set includes demographic information, vector infusion details, safety, efficacy, quality of life and burden of disease. Conclusions: The GTR is a global effort to ensure that long term safety and efficacy outcomes are recorded and analysed and rare adverse events, in a small patient population, are identified. Many unknowns on the long‐term safety and efficacy of gene therapy for hemophilia may also be addressed.